Efektivitas Pemerintahan Kelurahan dalam Penyelenggaraan Kebersihan Lingkungan (Studi Kasus Kawasan Kumuh Kelurahan Meranti Pandak) Kota Pekanbaru - Meiyuza Wulandari; Sujianto Sujianto (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Slum areas in Pekanbaru City are being addressed by the local government, including the Meranti Pandak Sub-district. This study aims to assess the effectiveness of the Meranti Pandak Sub-district government in maintaining environmental cleanliness in slum areas and to identify the inhibiting factors affecting its effectiveness (Case Study: Slum Area in Meranti Pandak Sub-district, Pekanbaru City). Environmental issues in this area are of major concern due to their impact on public health and quality of life. The study applies Duncan’s theory (as cited in Nurmalasari & Supriyadi, 2021), which highlights three indicators: goal achievement, integration, and adaptation. Data collection methods include observation, interviews, and documentation. The findings reveal that the sub-district government's efforts have not been fully effective. This is evident from poorly targeted programs, unequal service distribution among residents, low community participation, and weak monitoring and evaluation by the local authorities. Additional obstacles include unresolved waste management issues, limited budget, and non-permanent building structures. To improve effectiveness, the study recommends more focused program planning, sustainable community empowerment, and enhanced cross-sectoral coordination.